Análise crítica do discurso sobre a saúde do trabalhador: perspectiva do artesão do barro do Alto do Moura, Caruaru-PE. - Tavares, Janine Magaly Arruda (2014)
Researchers on the relationship between health and work point to an environmental determination on work activities, responsible for the health profile of the worker. There is a predominance in studies with indirect and quantitative data. Considering the three-dimensional model of Critical Discourse Analysis, proposed by Fairclough, were translated in a culturally appropriate language to lay populations and transformed into questions - stimulus scripts semidiretiva interview. In this sense, the objective of this study was to conduct a critical discourse analysis on the relationship between work and health-disease process, as well as explore the process of learning the craft, search the productive chain in the clay craft; understand the concepts of artisans about health and disease, focusing on the perception of artisans on the relationship between work environment and health; discuss the interpretation of the craftsmen on the municipal political relationship and health. In terms of method, the clay artisans in Alto do Moura Caruaru were interviewed using a logic of convenience sampling and saturation. The analysis was focused on the logical - semantic field, topics, interdiscursivity and representations of events. In conclusion, it is important to develop educational and political activities, and as a tool for speech processing in view of empowerment of these artisans, for the improvement of conditions of work and life.